Bibliometric Waqf Management in Indonesia - Heppy Purbasari; Bawono, Andy Dwi Bayu; Rangga Handika; Triyono (Universitas Muhammadiyah Surakarta, 2023)
A significant quantity of abandoned waqf lands in Indonesia is evidence that the optimal management of waqf has yet to be achieved. The primary objective of this study is to identify and analyze the existing research lacunae in prior studies, hence facilitating the delineation of future research directions. The employed research methodology utilizes a quantitative approach, wherein publications are quantified using the publish or perish tool and analyzed using the Vosviewer software afterward. This study employs the terms